2011
DOI: 10.5665/sleep.1254
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure: Evaluation of a Novel Therapy for Patients with Acute Ischemic Stroke

Abstract: The majority of acute stroke patients had sleep apnea. Auto-CPAP was well tolerated, appears to improve neurological recovery from stroke, and may represent a new therapeutic approach for selected patients with acute cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 35 publications
4
108
1
1
Order By: Relevance
“…In addition to the robust literature that supports the treatment of sleep apnea in the general population,20, 21 emerging data have suggested that patients with cerebrovascular disease in the early poststroke period derive neurological benefit from the treatment of sleep apnea. Three randomized controlled trials demonstrated improvements in the NIHSS score among patients treated in the acute stroke period; however, these studies were limited by small sample sizes (ranging from 32 to 55 patients) and short follow‐ups (ranging from 8 to 90 days) 2, 4, 7. In contrast to the favorable evidence supporting the diagnosis and treatment of sleep apnea in the acute stroke or TIA period, randomized controlled trials evaluating the use of CPAP in patients with subacute and chronic stroke have reported mixed results 3, 22, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the robust literature that supports the treatment of sleep apnea in the general population,20, 21 emerging data have suggested that patients with cerebrovascular disease in the early poststroke period derive neurological benefit from the treatment of sleep apnea. Three randomized controlled trials demonstrated improvements in the NIHSS score among patients treated in the acute stroke period; however, these studies were limited by small sample sizes (ranging from 32 to 55 patients) and short follow‐ups (ranging from 8 to 90 days) 2, 4, 7. In contrast to the favorable evidence supporting the diagnosis and treatment of sleep apnea in the acute stroke or TIA period, randomized controlled trials evaluating the use of CPAP in patients with subacute and chronic stroke have reported mixed results 3, 22, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea is common among patients with acute ischemic stroke and transient ischemic attack (TIA) (60–80%),1, 2 and preliminary data have suggested that treatment of obstructive sleep apnea with continuous positive airway pressure (CPAP) may improve patient outcomes 3. Several randomized controlled studies have evaluated the use of CPAP among patients with acute ischemic stroke or TIA, but they have been limited by short follow‐up or small sample size 1, 3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 There is convincing evidence that the majority of stroke patients have OSA, 5 and that early treatment with CPAP improves recovery from stroke 6 and reduces length of hospitalization. 7 Could the same be true of patients with prolonged mechanical ventilation?…”
Section: See the Original Study On Page 229mentioning
confidence: 99%
“…Three studies either included stroke patients as the full sample or had stroke as the primary outcome [38,43,46], and one study had mortality due to stroke as a secondary outcome [46]. Two of the four studies The method of randomisation was described and that method was appropriate…”
Section: Strokementioning
confidence: 99%